The correlation between students’ speaking anxiety and their speaking ability - Senny Plantika; Aryuliva Adnan (Journal of English Language Teaching, 2021)
This study aimed was to discover the level and the type of speaking anxiety among the student in speaking, and also to discover the correlation between speaking anxiety and their speaking ability at second-year students of English Department UNP. The correlation research was used in this research. The person who takes part inactivity of this research was 20 students of speaking class at English Department UNP in the academic year 2018. Questionnaire and interview were utilized in this examination to measure the correlation between the two aspects. The questionnaire was Foreign Language Anxiety Classroom Scale (FLCAS). Fear of negative evaluation was identified as the type of speaking anxiety, and the level of their speaking anxiety categorized at a medium level. After calculated the two aspects using SPSS 2.0, the result shows there is a negative correlation between students' speaking anxiety and their speaking ability. And it is correlated at -0.498 which means the correlation is in a moderate correlation.